Primer Exchange Reaction-Synthesized DNAzyme for the Sensitive Determination of an Oral Cancer Protein Biomarker. (24th May 2022) - He, Libang; Chen, Hao; Xu, Jue; Shao, Meiying
Abstract: A novel biosensing method is reported for the fluorescence determination of an oral cancer protein biomarker using primer exchange reaction (PER)-synthesized DNAzyme. Specifically, the target protein is captured by antibody-functionalized magnetic beads and recruits antibody-nucleic acid probes through immunoreactions to form sandwich-like complexes. After magnetic separation, the nucleic acid part of the antibody-nucleic acid probe participates in the PER as a catalytic hairpin, mediating the extension of primers. The extended primer forms the complete sequence of RNA-cleaving DNAzyme to effectively catalyze the cleavage of molecular beacons and produce a significantly amplified fluorescence signal. Taking interleukin 6 as a model biomarker, the method allows quantitative determination of the target in a wide linear range from 5 fg/mL to 500 pg/mL with a detection limit of 2.3 fg/mL and shows desirable specificity and usability in biological samples. More importantly, the complete DNAzyme is synthesized by the target-powered PER, which not only ensures the detection specificity, but also enables the decrease of background signals, thus greatly improving the sensitivity. Therefore, the method may provide a valuable tool for the determination of oral cancer protein biomarkers and may expand applications of DNAzyme in biosensing.